Fabrication of biodegradable composite – an implication of plasticizer - Kaiser, Mohammad Rejaul; Anuar, Hazleen; Maleque, Md. Abdul (2010)
This paper aims on the fabrication of fully biodegradable composite with the addition of plasticizer. For the fabrication of biodegradable composite, a twin screw extruder was used which provides a good blending of matrix, fiber and plasticizer. The percentage is varied from 5% to 40% for fiber and for plasticizer it is 5% to 20%. Higher percentage of plasticizer shows more difficulty during fabrication process of bio-composite. The results also showed that the addition of plasticizer reduces the melting and glass transition temperature of the composite which affects the processing parameter such as, temperature of different zones, rotation of the extruder screw, feed rate and production rate of the extruder. This paper also discussed on the suitable processing parameters for production of plasticized biodegradable composite.